Residency Program Website Content May Not Meet Applicant Needs - Sangrag Ganguli; Sheena W. Chen; Sam Maghami; Florina Corpodean; Paul P. Lin; Yolanda C. Haywood; Khashayar Vaziri; Juliet Lee; Hope T. Jackson (University Library System, University of Pittsburgh, 2024)
Background: Residency program applicants use a variety of resources during the application cycle. Program websites can vary substantially, and it is unclear how the website information is used by applicants. We aimed to determine the most popular information source used by applicants. We also sought to identify specific online content that was deemed important in the decision-making process. Methods: A survey was distributed to fourth-year medical students at an academic institution. Demographic information was collected, and the importance of various online resources was gauged using a Likert scale. Subgroup analysis was performed for procedural versus non-procedural specialty applicants. Results: 91 of the 169 fourth-year medical students (54%) completed the survey. The most utilized sources for the students were residency program websites (41%), the Fellowship and Residency Electronic Interactive Database (FREIDA) website (36%), and the Doximity website (14%). The most valued (Likert scale of 4 and 5) website content for the students included information on resident wellness (86%), resident fellowship acquisition (85%), faculty data (84%), residency location and resident lifestyle (81%), and application point of contact (79%). There were significant differences between what procedural specialty applicants deemed important versus what those applying to non-procedural specialties deemed important. Conclusion: Residency program websites are commonly used among applicants during the residency match process. Content on resident wellness was highly valued irrespective of specialty choice; however, this information was often not present on residency websites. These findings may help guide website content development initiatives for residency programs to reflect applicant needs more adequately.